External debt accumulation in Kyrgyzstan - Bodó Pál Bence („RIK-U” Kft., 2020)
Abstract. This paper aims at exploring the accumulation of external debt in Kyrgyzstan. Since the fall of the Soviet Union, the level of indebtedness has witnessed a severe deterioration further exacerbating the nation’s fragile and vulnerable economy, which is now among the most exposed to foreign lendings. The study suggests Kyrgyzstan boosts productivity, increases savings and fixes capital formation to get on a sustainable growth track that makes the country competitive in the global economic arena.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: Central Asia; Kyrgyzstan; external debt; indebtedness